Comparison of modeling with empirical calculation of diffuse and fugitive methane emissions in a Spanish landfill. (4th March 2019) - Sánchez, Carlos; de la Fuente, Maria del Mar; Narros, Adolfo; del Peso, Isabel; Rodríguez, Encarnación
ABSTRACT: One of the most significant environmental problems arising from landfills is the emission of methane into the atmosphere. In this study, methane emissions from a currently in-use Spanish landfill were modeled as well as being experimentally measured using a two-step method. The first step involved a qualitative walkover survey to detect where gases were being emitted on the surface of the landfill. The second stage comprised a quantitative analysis of these surface methane emissions at a selected number of points on the landfill surface using a specially designed flux chamber. The statistical analysis of the data obtained was based on the Sichel function and resulted in an average emission rate of 74.9 g·m −2 ·day −1, with 27.8 and 202.1 g·m −2 ·day −1 as the lower and upper limits of the 95% confidence interval, respectively. The total emission for the landfill, with an emitting surface of 335, 000 m 2, is 9.16 × 10 3  ton/yr. These values have been compared with those from three different models, with the model results being above the calculated mean emissions measured at the landfill, but below the upper confidence limit at 95%. Implications : One of the main environmental problems arising from the presence of landfills is the emission of biogas (which mainly contains methane and carbon dioxide) into the atmosphere. Several experimental methods as well as models have been developed to quantify these emissions. In this work, the authors have compared the results obtained using experimental measurements with those provided by some local and international models using the default parameters proposed. The results obtained from the experimental method are in accordance with those provided by the models, although the models could be slightly overestimating these emissions.